Relationship between loneliness and mental health indicators in the elderly during the COVID-19 pandemic - Schütz,Daiana Meregalli (2021)
Abstract Social isolation due to the global pandemic influenced not only the way how people interact, but it also brought a huge impact on the population’s mental health, regardless of their age. This study aimed to evaluate the intensity of symptoms of depression and anxiety, perceived stress, levels of loneliness, and psychological well-being in the elderly during social distancing due to the COVID-19 pandemic. The study included 86 elderlies, aged 60 to 90 years old (M=70.95; SD=7.08), living in the southern region of the country. They were interviewed by a WhatsApp video call and responded about symptoms of stress, anxiety, loneliness, depression, and positive mental health. The results showed that 55.8% had high stress symptoms, 18.6% anxiety symptoms, 16.3% depression symptoms, and 5.82% moderate to severe loneliness. It was found that participants who felt more alone had lower well-being scores.